Unlocking the biotechnological potential of Baltic microorganisms - Mazur-Marzec, Hanna; Grabowski, Łukasz; Węgrzyn, Alicja; Błaszczyk, Agata; Cegłowska, Marta; Dąbek, Przemysław; Farooq, Momina; Górecka, Ewa; Jurczak-Kurek, Agata; Kaczorowska, Anna-Karina; Kaczorowski, Tadeusz; Kataržytė, Marija; et al. (Frontiers in Microbiology, 2025)
Marine microorganisms are increasingly recognized as valuable sources of bioactive compounds and enzymes with diverse applications in biotechnology. Despite its relatively low overall biodiversity, the Baltic Sea harbours a variety of diatoms, dinoflagellates, bacteria (including cyanobacteria), fungi, and bacteriophages with notable biotechnological potential. These organisms produce metabolites with promising application in environmental remediation or as components of pharmaceuticals, nutraceuticals, cosmetics and biomaterials. Enzymes produced by Baltic Sea bacteria catalyse reactions of industrial relevance, while bacteriophages may provide novel tools for pathogen control in aquaculture or serve as sources of genes encoding for valuable enzymes. Although advances in high-throughput genomics and metabolomics have accelerated marine biodiscovery, Baltic Sea microorganisms remain largely understudied and underexploited by industry. This review synthesizes current knowledge on the biotechnological potential of the Baltic Sea microorganisms and highlights opportunities to bridge the gap between basic research and commercial application, particularly in the context of international frameworks such as the Nagoya Protocol.